Learning model and Islamic values of spatial design to support learning space model of Pesantren in Indonesia - Firmansyah, Rangga; Shaari, Nazlina; Ismail, Sumarni; Utaberta, Nangkula (Science and Engineering Research Support Society, 2020)
Learning space area is important as part of pesantren management. The learning model and Islamic values of spatial design determine design formulation of learning space area. This is interesting to discuss learning model and Islamic values of spatial design to support learning space model. This is important to study because it can affect the personality of students after graduating from pesantren. This article is literature review article with a qualitative approach. The results show that to create a learning space design, a review of the learning model and Islamic values of the pesantren is needed. However, the formulation of learning space design depends on what pesantren category you want to build. that is because between one pesantren and another pesantren have different types, curriculum,and learning methods. Besides, the application of aspects of Islamic principles that may be different also determines the formulation of learning space design.